Effect Of Environment Arrangement on Increasing Halal Tourism Visitors - Muflihatur Rohmah; Saif, Muhammad Burhan Abrori; Az-Dhifta Himmah Yasya (FEBI UIN Sunan Kalijaga Yogyakarta, 2022)
A healthy environment is an environment that has clean air, water and soil conditions and is free from pollution, and the area owned supports the creation of a healthy community. Automatically the environment will be protected from things that cause health problems, such as liquid, solid and gas waste. Also, avoid animals carrying disease germs, harmful chemicals, excessive noise pollution and other negative things. Conceptually, what can overcome environmental crises is to make eforts to preserve the environment by reforestation. The word preservation comes from